Discharge certificate of Peter Schlossen - Schlossen, Peter
U.S. Army discharge certificate, signed by Capt. James B. Swain, for Peter Schlossen, of Washington, D.C., ending his service in the Civil War.
Union soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Swain, James B. -- 1820-1895.; United States. -- Army -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Soldiers